Pengaruh Profitabilitas, Arus Kas, Leverage, dan Nilai Tambah Pasar terhadap Harga Saham pada Perusahaan Sektor Asuransi di Bursa Efek Indonesia - Intan Putri Prastikasari; RB Iwan Noor Suhasto; Shinta Noor Anggraeny (P3M Politeknik Negeri Banjarmasin, 2025)
This study aims to analyze the effect of profitability, cash flow, leverage, and market value added on stock prices of insurance companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach using panel data regression. The population and sample consist of insurance companies listed on the IDX during the 2019–2023 period. The sampling technique used is purposive sampling, resulting in 12 companies based on the availability of financial reports and annual stock price data. The data used are secondary data analyzed with EViews 13 software. The results show that profitability and cash flow significantly affect stock prices, while leverage and market value added have no significant effect. These findings suggest that investors tend to focus on financial indicators that directly reflect company performance, such as profit and cash flow, as they signal a company’s ability to generate returns and sustain operations. Conversely, high leverage is often associated with greater financial risk, and market value added receives less investor attention due to its long-term nature and limited relevance to short-term performance.